VARIABILITY AND HERITABILITY ESTIMATE OF 30 RICE LANDRACES OF LAMJUNG AND TANAHUN DISTRICTS, NEPAL - Anup Dhakal; Shishir Sharma; Amrit Pokhrel; Ankur Poudel (Indonesian Journal of Agricultural Science, 2020)
The variability in the rice landraces is the source of variation and offers substantial opportunity for the development of new varieties through the selection. Exploring diversity and variability of landraces is utmost for rice improvement. The objective of the study was to assess diversity indices, magnitude of genetic variability, heritability, genetic advance for the yield, and yield contributing traits. An experiment was carried out in alpha-lattice with 30 landraces, two replications in the Agronomy farm of IAAS, Lamjung Campus, during June-November, 2018. Shannon and Simpson's indices were calculated for 18 qualitative traits. The value of the Shannon and Simpson index ranged 0.15-1.41 and 0.07- 0.75, respectively. Landraces showed significant variations (p